'Popery, Palestrina, and Plain-tune': the Oxford Movement, the Reformation and the Anglican Choral Revival. Issue 1 (1st April 2014) - Cole, Suzanne
Abstract: Following an extended period of neglect, the early 1840s saw a dramatic revival of interest in English church music and its history, which coincided with the period of heightened religious sensitivity between the publication of Newman's Tract 90 in early 1841 and his conversion to Roman Catholicism in October 1845. This article examines the activities and writings of three men who made important contributions to the reformation of the music of the English church that took place at this time: Rev. Frederick Oakeley; Rev. John Jebb and the painter William Dyce. It pays particular attention to the relationship between their beliefs about and attitudes towards the English Reformation and their musical activities, and argues that such important works as Jebb's monumental Choral Service of the United Church of England and Ireland (1843) are best understood in the context of the religious and ecclesiological debates that were raging at that time. (1843) are best understood in the context of the religious and ecclesiological debates that were raging at that time.